2017
DOI: 10.1016/j.jcte.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of diabetes distress on digital interventions for diabetes management in vulnerable people with type 2 diabetes: A qualitative study of patient perspectives

Abstract: HighlightsInformants had several barriers towards the use of digital interventions.Diabetes distress may lead to poor adaption of digital interventions.An appropriate buddy may pave the way to better diabetes management.Informants preferred contact with a designated caregiver rather than digital interventions.Diabetes distress was a central issue requiring attention in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 49 publications
0
31
1
1
Order By: Relevance
“…However, these findings are in contrast to the results of Mathiesen et al [ 13 ] in their trial about the influence of technology interventions on T2D distress. They attributed their findings to the vulnerability of T2D patients facing tailored digital interventions, resulting in an increase in distress, such as “suffering informational confusion, experiencing digital alienation, and missing the human touch”, mainly because “navigating a complex digital portal on diabetes might be more challenging than simply accessing the site” and the digital caregivers’ approach.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, these findings are in contrast to the results of Mathiesen et al [ 13 ] in their trial about the influence of technology interventions on T2D distress. They attributed their findings to the vulnerability of T2D patients facing tailored digital interventions, resulting in an increase in distress, such as “suffering informational confusion, experiencing digital alienation, and missing the human touch”, mainly because “navigating a complex digital portal on diabetes might be more challenging than simply accessing the site” and the digital caregivers’ approach.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors have already demonstrated that technological devices could enhance engagement, adherence, cost effectiveness and access to health interventions[ 7 , 8 ], having an impact on blood glucose control and T2D self-management[ 9 - 12 ]. However, review authors have are in disagreement about the benefits of this technology in T2D distress[ 13 , 14 ]. The primary aim of this review is to determine the impact of programs with technological interventions regarding disease management, not just as a communication alternative, on T2D distress through a DDS measurement study.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of participants perceived themselves as not being sick. This may be because diabetes is initially a silent disease with imperceptible symptom progression and distant long-term complications (Carolan, Holman, & Ferrari, 2015;Mathiesen et al, 2017;Powers, 2014). Furthermore, not perceiving oneself as sick might be interpreted as an avoidant coping strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not perceiving oneself as sick might be interpreted as an avoidant coping strategy. Studies have shown that people with low socioeconomic status tend to use avoidant coping as their primary coping strategy due to few resources (Christensen, Schmidt, Hougaard, Kriegbaum, & Holstein, 2006;Houle et al, 2016;Mathiesen et al, 2017). The avoidant coping strategy of participants might have been reinforced by diabetes being a silent disease and, moreover, by the provision of tacit practical support from the informal network.…”
Section: Discussionmentioning
confidence: 99%
“…83 There are many vulnerable people in the T2D community who perhaps will never be suited for digital therapeutics as an adjunctive therapy or to facilitate their care virtually. 84 Personal human interaction will continue to play an important part in the care for millions of people living with diabetes, no matter the progress and sophistication of these digital services. What these technologies will provide, however, is the human capacity to deal with the higher need vulnerable people for whom access to timely care is an issue.…”
Section: Evidence and Excusesmentioning
confidence: 99%